The Management Scientist : version 5.0 for Windows 95, Windows 98, and Windows NT - Anderson, David R.; Williams, Thomas A.; Sweeney, Dennis J. (Cincinnati, OH : South-Western College, 1999)
This book is about: Linear programming; Transportation problem; Shortest route; ...
Keywords: Windows NT server; Management; Data processing; Computer file; Windows 95.; Windows 98.; Management Scientist (Computer file); Industrial management -- Decision making -- Data processing